Acute Onset of Dizziness Caused by a Cavernous Malformation Lateral to the Fourth Ventricle: A Case Report - Wen-Chieh Yang; Jiun-You Chen; Kang-Hsi Wu; Han-Ping Wu (Pediatrics and Neonatology)
Dizziness, diplopia, and nystagmus may be nonspecific symptoms and in part attributed to central causes. We report a case with brain stem lesion and discuss these nonspecific symptoms. A 13-year-old boy presented to our emergency department with a lasting dizziness for 1 week and diplopia for 5 days. New onset horizontal nystagmus was also noted during the physical examination. A cavernous malformation in the right middle cerebral peduncle lateral to the fourth ventricle was suspected by brain computed tomography and confirmed by magnetic resonance imaging. Without progression of the lesion, conservative treatment and regular follow-up were performed. This case report demonstrates the importance of primary physicians paying attention to children with dizziness, diplopia, and nystagmus for considering possible central nervous problems.